CHANGING THE TEXT, CHANGING THE CLASSROOM: CONFIDENCE AND COMMUNICATION IN ELE - Eugenia Charoni (PEOPLE: International Journal of Social Sciences, 2026)
This presentation examines how the adoption of a new textbook in an intermediate–advanced low Español como Lengua Extranjera (ELE) course enhanced student confidence in oral and written communication. Following a mandated curriculum change prompted by program evaluation results, a textbook emphasizing authentic, socially relevant texts and implicit grammar review was implemented. The course was taught over two consecutive semesters using this material, ensuring consistency in instructional design and assessment practices. Students engaged with contemporary social issues—including immigration, equal pay, heritage speakers, and gender representation in STEM—through sustained oral and written interaction with the texts. Assessment included analytical essays, text summaries, formal and informal letter writing, oral presentations, and small-scale collaborative research projects conducted exclusively in the target language. Oral and written assignments were evaluated using standardized rubrics to ensure transparency, reliability, and consistency across sections. Analysis of student performance data and course evaluations indicates increased confidence in speaking and writing, higher levels of motivation, and strong overall student satisfaction. These findings suggest that when curricular change is necessary, deliberate and bold choices in instructional materials can positively impact student engagement and learning. Communicative texts aligned with students’ interests effectively support linguistic development while fostering confidence, critical thinking, and sustained engagement in the intermediate–advanced low ELE classroom.